Tissue culture of Grammatophyllum speciosum blume, the world largest orchid - Montria, N.; Niumthong, W.; Janpatiw, A. (My University, 2009)
Tissue culture technique was used for large scale propagation of Grammatophyllum speciosum Blume, the world largest orchid. Sterilized seeds were grown in Vacin and Went (VW, 1949) medium. The 6 months old of protocorms were cultured in VW medium supplemented with various organic substances. Different concentrations of 6-benzyladenine (BA) and 2,4-dichlorophenoxyacetic acid (2,4-D) were also applied. The results indicated that different mixtures of banana pulp, pineapple pulp, tomato pulp and Jew's Ear mushroom extract could promote protocorms development into seedlings. The size of protocorms increased in BA and 2,4-D treatment. However fresh mass was decreased and root development delay at the higher concentrations of BA. At low concentrations of 2.4-D, root were develop well while browning occurred at higher concentrations. Plantlets were acclimatized in the room temperature and coconut husk-ship used as a substrate for 2 weeks and plants grew well after transferred to the outside environment.
Keywords: Jew's Ear mushroom; Pineapple; Protocorm; Seed culture; Tiger orchid; Tomato